Écrits comptables et commerce interreligieux : les cas des registres d'Ugo Teralh de Forcalquier et de la compagnie Datini (xive-xve siècles) - Ingrid Houssaye Michienzi; Judith Olszowy-Schlanger (Les Cahiers de Framespa)
The accounting documents, directly issued from the practice of business, allow historians to penetrate at the heart of commercial collaborations between Christians and Jews, and between Christians and Mudéjars, in Western Europe and the Mediterranean Sea in the Late Middle Ages. This paper considers the tracks of economic exchanges, but also social and cultural ones, through the examination of the journal of Ugo Teralh de Forcalquier of 1330-1332, and of the accounting books of the companies of Francesco Datini settled in Majorca and in Valencia around 1390-1410. Often in perfect contradiction with the normative texts, aiming at a more and more important spatial segregation between the various religious groups, the papers of the practice of business allow historians to present a different interpretation of their relations and to bring to light a scale of common moral values.